Previous control of the special theoretical knowledges of students of high school physical culture - Ісаченко [Isachenko M.] Марія (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The level oftheoretical knowledge of students2nd yearof high schoolphysical culture. The efficiency ofthe diagnostic testof theoreticalknowledge of the studentsearly in the courseof the discipline«Theory andMethods of Physical Education». A meanlevel of basicknowledge on thesecond-year students, necessary for the development ofthe discipline «Theory andMethods of Physical Education». Results of the studyhighlight issues, poorly masteredby studentsinprevioussemesters ofstudysubjectsand make adjustments tothe contentof the lecture material, as well as tasks for independentwork of studentsin preparationfor seminars. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>